Illegal Oil Well Mitigation: Environmental Sustainability: Strengthening the Oil and Gas Accounting Information System - Hertati, Lesi; Umar, Haryono (Jati: Jurnal Akuntansi Terapan Indonesia, 2024)
This study focuses on exploring aspects of illegal mining in the Musi Banyuasin area, South Sumatra Province-Indonesia. The research includes green accounting, human resources, sustainable environment, and oil and gas accounting information systems. This study uses a qualitative descriptive approach with an exploratory method to explore the phenomenon in detail. Data were obtained through structured interviews, field observations, focus group discussions (FGDs), and supporting document reviews. The collected data were analyzed thematically to identify, review, and report findings based on interviews. The results of the study indicate that the application of green accounting practices, human resource management, and the use of accounting information systems in the oil and gas sector are important foundations for creating a sustainable environment. Sustainable environments not only support economic aspects but also social, cultural, and ecological aspects. This research implies that it contributes to the preservation of green vegetation, reducing greenhouse gas emissions and environmental damage. Theoretically, this research provides insight into the theoretical benefits of green environmental sustainability.